Prediction of difficult laparoscopic cholecystectomy while working up the patient for surgery - Nishant, Kumar; Bhutia, Phuchungla; Kumar Singh, Varun; Kharga, Bikram; Kumar Sharma, Barun; Jain, Nitin (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Introduction: Laparoscopic cholecystectomy [LC] has established itself as standard of care for gallstone disease. With the wide availability of expertise, complication rate and conversion rate both are coming down. Coupled with increase in patient awareness and easy accessibility of information, it is becoming increasingly difficult for surgical team to explain complication arising following surgery. A preoperative prediction can help ease doctor-patient relationship. Objective: To find out the predictors of difficult laparoscopic cholecystectomy while investigating the patient for surgery. Patient and methods: We selected 125 patients based on convenient sampling who underwent LC. A Likert type questionnaire was used to assess the difficulty. Weighted difficulty score [WDS] was calculated as the sum of product of parameter response and difficulty response score [WDS= ∑ (PR x DRS)]. Mean WDS was then compared against preoperative investigation findings. Results: Mean WDS was found to increase with raised leukocyte count as well as with altered liver function tests. Thickened gallbladder wall in ultrasonography had a positive correlation with difficulty in surgery but no association was found with the pericholecystic fluid. A larger size of stone, stone impacted at neck and a larger size of the impacted stone were all had a significant positive association with difficult LC but number of stones in GB had no impact on difficulty during surgery in our study. Altered liver echotexture and a contracted GB were the other factors which can predict a possible difficulty during LC. Conclusion: A careful watch on investigation which include leukocyte count, liver function tests and preoperative ultrasonography can help predict the difficulty, a possibility of conversion as well as complications. A discussion of these events with the patients and their relatives can create an atmosphere of mutual trust and better prepare to overcome of untoward events.